The Role of the Dumai City National Narcotics Agency in the Rehabilitation of Drug Abuse Victims - Safitri, Safitri; Habibie, Dedi Kusuma (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Drug rehabilitation is a treatment process for narcotics abuse to restore or develop the physical, mental and social abilities of the sufferer concerned. Apart from recovering, rehabilitation is also a treatment or care for narcotics addicts so that people with an addiction can recover from their addiction to narcotics. This research aims to find out the role of the Dumai City National Narcotics Agency in the rehabilitation of drug abusers and to find out the inhibiting factors faced in rehabilitating drug abuse victims at the Dumai City National Narcotics Agency. This research uses qualitative research methods with a descriptive approach. This research refers to the organizational role theory of aromatic D and Sudrajat AR, which has four approach indicators: division of work, departmentation, distribution of authority, and coordination. The results of this research show that the role played by the organization in achieving the organization's goals is quite good. However, coordination in the field of prevention is still not optimal. The inhibiting factors are the lack of rehabilitation facilities and the long travel distance. In this way, it is hoped that the Dumai City National Narcotics Agency will emphasise coordination more and improve rehabilitation facilities.